2017
DOI: 10.5812/jamm.42356
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Loneliness and Associated Factors Among Iranian College Students During 2015

Abstract: Background: University students are the developers of their nations' future and make up a significant number of young people. The number of students is increasing as universities and higher education centers develop. Hence, paying attention to student's physical and mental health is among the most important issues. The aim of the present analytical cross-sectional study was to determine the epidemiological pattern of loneliness and related factors among Maragheh University of Medical Sciences students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 11 publications
4
19
1
Order By: Relevance
“…Turkish male students experience more loneliness. 21,25,43 Unlike our results, in a study conducted by Alaviani et al 44 it was found that the level of loneliness in Iranian female students was more than male, which is the opposite of the current results. This difference may be related to the difference in the size of the sample and/or the differences in cultural and social factors.…”
Section: Discussioncontrasting
confidence: 99%
“…Turkish male students experience more loneliness. 21,25,43 Unlike our results, in a study conducted by Alaviani et al 44 it was found that the level of loneliness in Iranian female students was more than male, which is the opposite of the current results. This difference may be related to the difference in the size of the sample and/or the differences in cultural and social factors.…”
Section: Discussioncontrasting
confidence: 99%
“…An elevated level of loneliness resulting from quarantine has been reported [37], [23]. Loneliness also had been DOI 10.18502/kss.v7i1.10210 ICoPsy known as a significant predictor of depression [6], especially among college students [27], [28], [26], [29].…”
Section: Covid-19 Risk Factors: Perceived Stress and Loneliness On Depressionmentioning
confidence: 99%
“…Loneliness has also been identified as a risk factor for depression and may be particularly prevalent during the pandemic [25], [6], [26], [23]. Feeling disengaged from social connection due to social distancing and isolation may make one feel lonely and vulnerable, especially among college students [27], [6], [28], [29]. The current study then will focus on exploring both perceived stress and loneliness as two predictors of depression.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown a high prevalence of loneliness among higher education students with as many as 20–50% of students experiencing loneliness (Alaviani, Parvan, Karimi, Safiri & Mahdavi, 2017; Dagnew & Dagne, 2019; Diehl, Jansen, Ishchanova & Hilger‐Kolb, 2018; Friderichsen, 2017). Specifically, Alaviani and colleagues (2017) used the revised UCLA Loneliness Scale and found that 50% of a sample of Iranian Medical Science students (N = 323) could be classified as being moderately lonely, while 32% of the students could be classified as severely lonely. Dagnew and Dagne (2019) also used the revised UCLA Loneliness Scale among Ethiopian Medical and Health students (N = 404) and found that 50% of the students experienced loneliness.…”
Section: Introductionmentioning
confidence: 99%
“…Dagnew and Dagne (2019) also used the revised UCLA Loneliness Scale among Ethiopian Medical and Health students (N = 404) and found that 50% of the students experienced loneliness. Both studies found a significant effect of gender with female students experiencing a higher degree of loneliness than male students (Alaviani et al ., 2017; Dagnew & Dagne, 2019). Diehl and colleagues (2018) used the six‐item De Jong Gierveld Loneliness Scale among German university students (N = 689) and found that 32% could be classified as being moderately lonely and 3% severely lonely.…”
Section: Introductionmentioning
confidence: 99%